(untitled) (Intent Research Scientific Journal, 2023)
Distance education has emerged as a flexible and accessible way to teach various subjects, including programming. While it offers numerous advantages, this paper sheds light on the disadvantages of teaching programming in a distance education format. We explore the unique challenges that distance education faces in imparting programming skills and discuss the potential limitations that educators and learners may encounter in this context.